Increased inhibitory synaptic activity in the hippocampus (CA1) of genetic absence epilepsy rats: Relevance of kindling resistance - ONAT, FİLİZ; GÜLHAN, REZZAN (ELSEVIER, 2016)
Purpose: Genetic absence epilepsy rats from Strasbourg (GAERS), a well-validated genetic rat model for typical absence epilepsy, are known to manifest a resistance to secondary generalization of abnormal focal electrical activity evoked by kindling. The mechanism of this resistance is still unclear. In order to understand the possible mechanism of kindling resistance, we investigated for the first time, the differences of short-term synaptic plasticity by using a paired-pulse paradigm as an indicator of GABAergic activity in CM region of hippocampus in GAERS and non-epileptic Wistar rats in-vivo. Methods: Rats were subjected to kindling process, basolateral amygdala was stimulated twice a day, with a supra-threshold current, until they displayed limbic or convulsive seizures. One hour after the last kindling stimulation, evoked field potentials from CA1 pyramidal layer of hippocampus were recorded in-vivo under urethane anesthesia. Results: In response to supra-threshold kindling stimulations GAERS showed a significantly delayed kindling progression and displayed a significant increase in hippocampal excitability at early stages of kindling that is the critical for the development of convulsive seizures. In control rats that were not received kindling stimulation, paired-pulse depression (PPD) was significantly pronounced in GAERS with respect to the Wistar group. During the kindling course, PPD was gradually reduced in the Wistar rats as kindling progression was advanced. However in GAERS, PPD ratios were not significantly changed at early stages of kindling. When GAERS reached convulsive stage, their PPD ratios became similar to that of Wistar rats. Discussion: The increased inhibition in paired-pulse responses at early stages of kindling in GAERS suggests the role of augmented GABAergic activity as one of the underlying mechanisms of kindling resistance observed in genetic rat models of absence epilepsy. (C) 2016 Published by Elsevier B.V.
Keywords: GABA; GAERS; Absence epilepsy; Paired-pulse depression; Electrophysiology; In-vivo; WAVE DISCHARGES; ELECTRICAL-STIMULATION; UNDERLYING SPIKE; DENTATE GYRUS; GRANULE CELLS; SEIZURES; MODEL; RECEPTOR; MECHANISMS; GABA(A)